Intrinsic and Extrinsic Motivations on Willingness to Communicate Among Iraqi Learners - Sajad Kadhim Faraj Al-Jabari Azad (Academia Open, 2025)
General Background: Motivation is a cornerstone of second language acquisition (SLA), shaping learners’ engagement and communicative competence. Specific Background: In contexts like Iraq, where English is taught as a foreign language (EFL) with limited authentic exposure, extrinsic motives—such as exams and societal expectations—often outweigh intrinsic interest, potentially constraining learners’ willingness to communicate (WTC). Knowledge Gap: While studies in Asian and Western EFL/ESL settings have explored motivation–WTC links, little empirical research addresses pre-intermediate Iraqi learners, a group particularly vulnerable to anxiety and rote-based instruction. Aims: This study investigated which type of motivation dominates among Iraqi EFL students, how motivation relates to WTC, and which orientation predicts it most strongly. Results: Data from 40 female learners in Maysan revealed extrinsic motivation dominance (M = 29.03) over intrinsic (M = 19.93), yet intrinsic showed a stronger correlation with WTC (r = .36, p < .01) and was the only significant predictor (β = .33, p < .001), explaining 10.17% of variance. Novelty: These findings challenge assumptions that extrinsic pressures drive communication in EFL, highlighting instead intrinsic motivation’s centrality. Implications: Pedagogically, fostering intrinsic interest through autonomy-supportive, communicative tasks may enhance WTC and address cultural-educational constraints in Iraq. Highlights: Intrinsic motivation is a stronger predictor of WTC than extrinsic factors. Iraqi EFL learners show dominance of extrinsic over intrinsic motivation. Pedagogical focus on intrinsic interest can enhance communicative competence. Keywords: Intrinsic Motivation, Extrinsic Motivation, Willingness to Communicate, Iraqi EFL Learners, Second Language Acquisition